3D printed cellular cathodes with hierarchical pores and high mass loading for Li–SeS2 battery. (20th July 2020) - Shen, Chunli; Wang, Teng; Xu, Xu; Tian, Xiaocong
Abstract: To satisfy the vast demand on high energy density for the next-generation electrochemical energy storage system, lithium selenium-sulfur (Li-Sex Sy ) battery has drawn ever-growing interest with great advantages of low cost and promising capacity. However, its practical application with high areal mass loading of electrode manufacturing is still challenging. Here, we firstly print three-dimensional (3D) freestanding electrodes for Li–SeS2 batteries via direct ink writing based on the high-solid-content ink. The characteristic rheology properties of the ink possess excellent printability and enable the stable extrusion of 3D-printed cellular scaffold. In such a printed architecture, the low-cost commercial conducting ketjenblack (KB) with abundant pores is selected as the host material for selenium sulfide. For a well-controlled 3D-printed KB/SeS2 electrode, the areal SeS2 loading reaches 7.9 mg cm −2 . More importantly, with the hierarchical porosity engineering, the 3D-printed cellular KB/SeS2 cathode delivers a high initial discharge capacity of 9.5 mA h cm −2  at 1.8 mA cm −2 and high Coulombic efficiency of 96% over 80 cycles is achieved with such high mass loading. This 3D-printed Li–SeS2 battery electrode may guide more energy storage systems with ultrahigh capacity to the practical application. Graphical abstract: Image 1